The Effect of Financial Distress, Leverage, and Managerial Ownership on Accounting Conservatism In Property Companies Listed on the IDX in 2021-2023 - Marnita HASUGIAN; Rahima PURBA; Fitri Yani PANGGABEAN (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to determine the effect of Financial Distress, Leverage, and Managerial Ownership on Accounting Conservatism in property companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study uses an associative strategy to determine the relationship between two or more variables. The data in this study uses secondary data. The population in this study amounted to 92 companies. Sampling and sample size determination in this study were carried out using the Purposive Sampling method, resulting in a sample of 29 entities. The analytical approach uses multiple linear regression analysis, the coefficient of determination, the classical assumption test, and descriptive statistical data analysis. Use the t-test and F-test to test the hypothesis. This study found that Financial Distress has a significant effect on accounting conservatism, Leverage has no significant effect on accounting conservatism, and Managerial Ownership has no significant effect on accounting conservatism. The F-test in this study concluded that only Financial Distress has a significant effect on Accounting Conservatism, while Leverage and Managerial Ownership have no significant effect on Accounting Conservatism.